PENGARUH CORPORATE IMAGE DAN PERCEIVED VALUE TERHADAP KEPUTUSAN MUZAKKI MEMBAYAR ZAKAT DI LAZ LMI SUMATERA SELATAN - Zulfikri Zulfikri; Rinol Sumantri (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2022)
This research has a goal, namely to determine the effect of corporate image, perceived value on muzakki's decisions in distributing zakat at LAZ LMI Suamtera Selatan with an associative approach with quantitative research and the data used is in the form of primary and secondary resulting from questions answered by respondents then processed and analyzed by multiple linear regression. The results of the study show that corporate image and perceived value have a considerable and significant influence on the muzakki's decision to distribute zakat at LAZ LMI, namely 67.7%, and the remaining 32.3% is influenced by other factors not explained in this study. This means that if there is an increase in corporate image and perceived value, it will increase the muzakki's decision to pay zakat, and vice versa if there is a decrease in corporate image and perceived value, it will reduce the muzakki's decision to pay zakat. For future researchers, it is hoped that this can be used as a reference to be able to continue and build on variables that are able to condition the state of the population and with mature techniques.